2007
DOI: 10.1261/rna.220407
|View full text |Cite
|
Sign up to set email alerts
|

The role of the S1 domain in exoribonucleolytic activity: Substrate specificity and multimerization

Abstract: RNase II is a 39-59 exoribonuclease that processively hydrolyzes single-stranded RNA generating 59 mononucleotides. This enzyme contains a catalytic core that is surrounded by three RNA-binding domains. At its C terminus, there is a typical S1 domain that has been shown to be critical for RNA binding. The S1 domain is also present in the other major 39-59 exoribonucleases from Escherichia coli: RNase R and polynucleotide phosphorylase (PNPase). In this report, we examined the involvement of the S1 domain in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 55 publications
(78 reference statements)
5
52
0
Order By: Relevance
“…In order to determine the binding curve, RNA-binding of the purified protein was analyzed in a UV-cross-linking assay using increasing amounts of PNPase. As shown in Figure 6A, while the E. coli enzyme displayed a saturation binding curve with a K d of 11 nM, in agreement with previous reports (BermudezCruz et al 2002;Schubert et al 2004;Stickney et al 2005;Amblar et al 2007), an apparent sigmoid curve, typical of cooperative binding, was observed for the human enzyme. The K d observed for the human PNPase was z16 nM.…”
Section: Human Pnpase Displays Different Rna-binding Properties Compasupporting
confidence: 92%
“…In order to determine the binding curve, RNA-binding of the purified protein was analyzed in a UV-cross-linking assay using increasing amounts of PNPase. As shown in Figure 6A, while the E. coli enzyme displayed a saturation binding curve with a K d of 11 nM, in agreement with previous reports (BermudezCruz et al 2002;Schubert et al 2004;Stickney et al 2005;Amblar et al 2007), an apparent sigmoid curve, typical of cooperative binding, was observed for the human enzyme. The K d observed for the human PNPase was z16 nM.…”
Section: Human Pnpase Displays Different Rna-binding Properties Compasupporting
confidence: 92%
“…Instead, these enzymes have a specific RNA chain size limit that, once approached, causes the release of the remaining RNA chain. As an example, the released chain lengths produced by RNase II and RNase R were found to be 3-5-mers (Cheng and Deutscher 2002) or 4-6-mers (Amblar et al , 2007, and 2-3-mers (Cheng and Deutscher 2002;Vincent and Deutscher 2006) or 1-2-mers (Amblar et al 2007), respectively. The mechanistic basis for this size limit was explained nicely by structural insights provided by the example of RNase II, where binding of a relatively long RNA molecule is important for stabilizing the catalytic complex (Cheng and Deutscher 2002;Frazao et al 2006;Vincent and Deutscher 2006;Amblar et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…PNPase is a phosphate-dependent exonuclease that acts as a trimer (Pruijn 2005). The recent available structure of RNase II highlighted the mechanism of degradation of this hydrolytic enzyme (Amblar et al , 2007Frazão et al 2006;Zuo et al 2006). Homologs of these exonucleases exist in eukaryotic exosomes (a multiprotein complex of exonucleases), and they were shown to be essential in the processing of noncoding RNAs (Houseley et al 2006).…”
Section: Introductionmentioning
confidence: 99%